Bending Performance of Epoxy Adhesive Joints of Prefabricated Concrete Elements - Peng, Hongbo; Zhang, Zhongya; Zou, Yang; Guo, Jincen; Zhang, Xiaoyan; Zeng, Xingqi (Frontiers in Materials, 2022)
The assembly construction of prefabricated UHPC elements can well balance quality reliability and construction convenience, thus it has excellent application prospects in bridge engineering. The joints between prefabricated elements are the key to ensuring the overall force performance of the structure, which directly determine the load-bearing capacity and the life of structure. To clarify the bending behavior of epoxy adhesive joints between prefabricated UHPC elements, four groups of 12 bending tests were carried out with different interface treatment forms as parameters. The failure modes, load-deflection curves, and ultimate bending strength of the interface were investigated. The results reveal that the interfacial failure modes mainly include the interfacial stripping failure of epoxy-UHPC surface, steel fibers and fine aggregates into UHPC surface by pulling out, and tensile damage of UHPC at the root of key teeth on the side of the keyway interface. The load-deflection curves of all specimens exhibit the two-fold lines form. The load tends to rise linearly during the loading phase, and there is no yielding phase before the failure. The load-carrying capacity of the specimen is lost immediately after the failure, and no reliable residual strength is available except for the keyway interface. In addition, the bending strength of rough interface, groove interface, and keyway interface are respectively improved by −24.02, 2.34, and 4.64%, compared with the natural interface. So it is recommended that the joint between prefabricated UHPC elements take the form of keyway interface. Finally, a simplified force model of the keytooth adhesive joint is proposed, and a calculation formula for the flexural bearing capacity is established based on the principal of Mohr’s circle, based on the experimental results and theoretical analysis. The mean ratio of the proposed adhesive joint calculation equation to the experimental results was 0.925 with a standard deviation of 0.065.